Strategi Dinas Pariwisata dalam Mempromosikan Wisata Daerah pada Masa Pasca Pandemi Covid-19 di Kabupaten Pacitan - Wulan Oktafiantika; Bambang Triono; Ekapti Wahjuni DJ (Institut Pemerintahan Dalam Negeri (IPDN) Kampus Sumatera Barat, 2022)
Tourism is a tertiary need. A person will do tourism if all the primary and secondary conditions are met. The pandemic of Covid-19 has been running for two years, from early 2000 to the end of 2021. It causes many traumas to human life. Thus, the researchers took three formulations of the problem, namely: how the strategy used by the Tourism Office in promoting local tourism during the post-Covid-19 pandemic in Pacitan Regency, the factors inhibiting the strategy of the Tourism Office in promoting regional tourism during the post-Covid-19 pandemic, and what solutions conducted by the Tourism Office to overcome the inhibition. The writing aims to describe the Office's efforts to develop tourism after the pandemic era. The result shows that the strategies conducted by the Tourism Office are suitable with the theories: advertising, promoting, publishing, and self-purchasing. There are two inhibiting factors, internal and external factors. The internal factors are the lack of human resources in management, while the external factors are caused by the limited number of tourists in tourism destinations. The Tourism Office's solutions are conducting an evaluation meeting every month, training for tourism management, and training for promotion to bring up creative ideas to attract tourists.